2020
DOI: 10.3390/cancers12113472
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mutation Profiles with Postoperative Survival in Patients with Non–Small Cell Lung Cancer

Abstract: Findings on mutations, associated with lung cancer, have led to advancements in mutation-based precision medicine. This study aimed to comprehensively and synthetically analyze mutations in lung cancer, based on the next generation sequencing data of surgically removed lung tumors, and identify the mutation-related factors that can affect clinical outcomes. Targeted sequencing was performed on formalin-fixed paraffin-embedded surgical specimens obtained from 172 patients with lung cancer who underwent surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In line with previous studies [ 49 , 50 ], the changes in mutational burden were also observed during the disease progression in our study. Guo and colleagues reported decreasing VAF percentages (10% or more) for EGFR alterations in several patient samples after surgical treatment [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [ 49 , 50 ], the changes in mutational burden were also observed during the disease progression in our study. Guo and colleagues reported decreasing VAF percentages (10% or more) for EGFR alterations in several patient samples after surgical treatment [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have focused on 53 major genes that have been shown to be involved or implicated in lung cancer formation ( Supplementary Table S1 ), which are described in The Cancer Genome Atlas [ 15 , 16 ]. Targeted deep sequencing was performed as described previously [ 17 , 18 , 19 , 20 , 21 ]. Briefly, primer design and library construction were carried out using Ion AmpliSeq™ Designer and Library Kit 2.0, respectively (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Next‐generation sequencing (NGS) can reveal the whole gene profile of patients with lung cancer 12‐15 . The Oncomine Dx Target Test Multi‐CDx system, which was approved by the Food and Drug Administration in June 2017 in the United States, was approved in Japan as a companion diagnostic test in June 2019.…”
Section: Introductionmentioning
confidence: 99%